An Exploration of Employment-Related Personal Projects Undertaken by Women on Probation and Parole. (January 2021) - Roddy, Ariel L.; Morash, Merry; Hoskins, Kayla M.
This qualitative research investigates the extent to which 401 women under supervision identify employment-related personal projects (i.e., actions taken to achieve abstract goals) as a way to make their lives better. Psychological theory about personal projects and feminist pathways theory guided the analysis. Findings reveal how project meaningfulness, self-efficacy, and social support to carry out the project affect well-being. Structural barriers, disability, and transportation issues were also identified. Findings suggest that many women pursue and benefit from employment-related projects. Correctional agents can assist women by helping them choose meaningful projects and providing information, resources, and social support.